HADITS TEMATIK TENTANG URGENSI KOMUNIKASI KELOMPOK - Fakhri Fakhri (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2017)
Man is a social species in which he needs the help of others, so that interaction with others to form groups/communities to meet their needs is inevitable. Communication is unavoidable to keep the relationships within a group or binding relationships between individuals in a group or groups of individuals. The author will examine how Islam arranges group communication to its believer. In this case the authors present some thematic Hadith about the urgency of the communication group.